Knowledge and perception about climate change among healthcare professionals and students: A cross-sectional study - La Torre, Giuseppe; De Paula Baer, Alice; Sestili, Cristina; Andrea Cocchiara, Rosario; Barbato, Domenico; Mannocci, Alice; Del Cimmuto, Angela (South Eastern European Journal of Public Health (SEEJPH), 2020)
Aim: The aim of this study was to assess knowledge on Climate Change (CC) and related consequences among students and professionals of healthcare setting. Methods: A cross-sectional study involving 364 people was conducted. The survey was performed at Sapienza University (Rome) using questionnaire previously developed and validated by the same research group. Results: Findings indicate awareness about CC and its effects and correct identification of practices that could help to mitigate its repercussions. The majority of the participants believed that CC had an impact on the health of humans (96.7%), animals (99.5%) and on the environment (99.7%). Results from the multivariate analysis regarding overall knowledge, show an increased odd in professionals (OR=2.08; 95%CI=1.02-4.26), individuals from the North (OR=3.34; 95%CI=1.37-8.15) and from the Center (OR=2.07; 95%CI=1.17-3.66). Regarding factors able to modify Earth's climate, correct answer had higher odds of being chosen by professionals (OR=2.83; 95%CI=1.41–5.70), and from individuals from South/Islands than by the ones from the Center (OR=0.65; 95%CI=0.40-1.06). The main sources of information resulted to be TV and school/university. Conclusions: These new evidences could guide policymakers on increasing the awareness of the population about this fundamental subject. Funding: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Author contributions: Conceptualization, G.L.T. and A.D.C..; Methodology, G.L.T. and A.M..; Formal Analysis, A.D.P.B., C.S., R.A.C., D.B.; Investigation, A.D.P.B., C.S., R.A.C., D.B.; Data Curation, A.D.P.B., C.S.; Writing – Original Draft Preparation, R.A.C., D.B.; Writing – Review & Editing, R.A.C., D.B., A.M..; Supervision, G.L.T..; Project Administration, G.L.T. Conflicts of interest: None declared